The role of blood type in COVID-19 response: Contributions to resistance and susceptibility (Research, Society and Development, 2025)
Representing one of the most significant pandemics in modern history, the new coronavirus (SARS-CoV-2) and its relationship with ABO blood types, already known for various other diseases and other members of the coronavirus family, are currently under investigation. The objective of the present study is to elucidate how the relationships of resistance and susceptibility to COVID-19 vary according to each ABO blood type. In the methodology, a search was conducted in 4 databases, using the PICO strategy with combinations of descriptors: "Blood Type and COVID" and its relevant variations, such as "ABO blood group COVID-19", "Rh factor SARS-CoV-2", "blood group susceptibility COVID-19", and "blood group severity COVID-19". Initially, 45 studies were found, but after applying exclusion criteria, 19 studies remained for analysis. A significant portion of the authors identified greater susceptibility to infection in individuals with blood type A and greater resistance to the virus in group O. However, the relationships with clinical outcomes are still conflicting. Despite the need for greater contributions from the scientific and medical community, it was possible to draw correlations that characterize group A, especially individuals with Rh-positive blood, as the group at higher risk for complications. This knowledge is important for the proper management of patients and for predicting outcomes in cases of SARS-CoV-2 infection.